Kajian terhadap Penilaian Kinerja dan Budaya Organisasi - Osrita Hapsara; HJ. Atikah (Jurnal Aplikasi Manajemen, 2010)
Culture of organization needs to be known by leaders or managers to facilitate them in determining the attitude, how they should act so that its members can be directed toward the attitudes and behavior helping to achieve organizational goals. To measure the achievement of organizational goals that have been established it is very important for companies to have a performance concept that can not be separated from the culture of the organization itself. Performance appraisal is a process of evaluation of staff using the tool, comparing it with the standard. How to assess the effectiveness evaluation with essay method, the definition of compensation assessment ,checklists direct assessment of spaciousness, assessment, based on behavioral assessment ,based on critical incident analysis and assessment of the effectiveness of assessments. The goal of certification is the assessment of staff, as well as define the article development personnel and to do training, in general, cannot be separated from the culture of the Organization itself.Keywords: performance, appraisal , and organizational culture